Learning to teach in a situated learnership model of teacher education: a case study of the support provided by mentor teachers in the process of learning to teach - Borello, Loredana Paola (My University, 2019)
In the South African education landscape, an apprenticeship/learnership model of teacher education is gaining traction, particularly in the private education sector. There is a general perception that student teachers who are immersed in a school context daily will gain a better understanding of the process of learning to teach. However, this assumption has not been empirically tested. The purpose of this qualitative research was to understand how mentors of student teachers in a learnership programme in a private school in South Africa, understand and support the process of learning to teach, both theoretically and in practice. The mentors’ criteria for good teaching and what is important in the mentoring interactions determines the kind of Zone of Proximal Development they are able to create in the mentoring interactions, specifically in the provision of feedback to student teachers on the lessons they teach. The research was conducted with three mentor teachers, each responsible for mentoring a student teacher in their subject area, mathematics. The research employed consisted of audio-recorded interviews with the mentors, as well as audio-recorded feedback sessions between the mentors and their respective student teachers after the mentor observed the student teaching two lessons. The results show that there is a variation in the forms of knowledge and support provided to the student teachers. The mentors’ support of the student teachers mostly focused on general pedagogical support in the form of tips and general classroom management advice. The more substantive mentorship, which focuses on the explicit communication of instructional design and pedagogical reasoning, was limited in some instances or not evident at all in other instances. A formal cognitive mentorship programme is recommended to effectively support student teachers in the process of learning to teach and to develop them into professional teachers. Such a programme should interrogate the mentors’ own assumptions about teaching, help them to understand the processes and complexities of learning to teach and guide them on how to design opportunities for making the pedagogical reasoning behind teaching choices explicit to student teachers.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Education by Creative Writing to the Faculty of Humanities, University of the Witwatersrand, 2019
Keywords: Teachers|xTraining of; Training needs--South Africa; Education--Study and teaching